Chronicity and Mental Health Service Utilization for Anxiety, Mood, and Substance Use Disorders among Black Men in the United States; Ethnicity and Nativity Differences - Mays, Vickie M. (Healthcare (Basel), 2018)
This study investigated ethnic and nativity differences in the chronicity and treatment of psychiatric disorders of African American and Caribbean Black men in the U.S. Data were analyzed from the National Survey of American Life, a population-based study which included 1859 self-identified Black men (1222 African American, 176 Caribbean Black men born within the U.S., and 461 Caribbean Black men born outside the U.S.). Lifetime and twelve-month prevalence of DSM-IV mood, anxiety, and substance use disorders (including Bipolar I and Dysthmia), disorder chronicity, and rate of mental health services use among those meeting criteria for a lifetime psychiatric disorder were examined. Logistic regression models were employed to determine ethnic differences in chronicity, and treatment utilization for disorders. While rates of DSM-IV disorders were generally low in this community sample of Black men, their disorders were chronic and remained untreated. Caribbean Black men born in the U.S. had higher prevalence of Post-Traumatic Stress Disorder, Major Depressive Disorder, and Alcohol Abuse Disorder compared with African American men. Foreign born Caribbean Black men experienced greater chronicity in Social Phobia and Generalized Anxiety Disorder compared to other Black Men. Utilization of mental health service was low for all groups of Black Men, but lowest for the foreign born Caribbean Black men. Results underscore the large unmet needs of both African American and Caribbean Black men in the United States. Results also highlight the role of ethnicity and nativity in mental disorder chronicity and mental health service utilization patterns of Black men.